Analysis Of Added Value Of Organic Certified Premium Arabica Coffee Beans And Organic Certified Premium Arabica Coffee Beans In Central Aceh - Bagio Bagio; Emmia Tambarta Kembaren; Ira Manyamsari (JASc (Journal of Agribusiness Sciences), 2021)
Indonesia was known as the 4th largest coffee exporting country in the world after Brazil, Vietnam and Colombia. Brazil has the highest production of arabica coffee in 2008 to 2013. Aceh is one of the central production of Arabica Coffee in Indonesia. The data from BPS showed that there are six districts which are known as the central production of coffee Aceh. Aceh Tengah districts known as the main area of coffee production among the six districts. The area of coffee plantations, production and productivity in this districs showed an increasing trend in five years. This study aims to determine the differences in added value of gayo premium coffee beans with organic certified and gayo premium coffee beans without organic certified. This research was taken in Aceh Tengah District. The data in this research was collected used were in-depth interviews methods with some decision makers in trade office, agriculture service, plantation service, coffee expert staff and green been coffe agro-industry which had the largest export quota in Aceh Tengah District, KBQ Baburrayyan. To analyze the added value of the Gayo coffee commodity the Hayami Method analysis tool was used. This study shows that the added value of organic certified premium coffee beans is Rp. 34.419/Kg with 49,51% ratio which was higher than the added value ratio of premium coffee beans without organic certified as much Rp. 30.893 with 46,81% ratio.